ALTERNATIVE VIEWS ON THE PARTICIPATION OF NON-EURO ZONE COUNTRIES AT THE BANK UNION - DONATH, Liliana; MIHUTESCU CERNA, Veronica (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0001 The reformation of the bank systems’ regulation and supervision in The European Union was founded on a macroprudential approach to monitor systemic risks and the vulnerabilities in a more effective way. Considered as the backbone of the new macroprudential supervision architecture, the Bank Union raises intense debates among the catching up economies. The fact that there are few studies on the costs and benefits of joining the Bank Union for the Central and Eastern European countries, explains the different views of the decision makers concerning this issue. The study stresses the manner in which macroprudential policies were implemented in Romania, as a particular case among the CEE countries, and the extent of their contribution to mitigating vulnerabilities and maintaining financial stability. The paper summarises the main arguments in favour of joining the Bank Union by emphasising the Romanian monetary authorities’ stance compared to those of the neighbouring CEE countries. JEL classification: E58